2018
DOI: 10.1002/pon.4820
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for depression in Lithuanian breast cancer patients

Abstract: KEYWORDSbreast cancer, depression, delivery of diagnosis, psychocial, risk factors, support 1 | BACKGROUND Breast cancer is the second most common cancer in the world and the most frequent cancer among women. 1 This disease is one of the most stressful events in someone's life, what can trigger a depression. 2 In investigations made worldwide tendency was observed, that older, not employed, low educated and single patients are more prone to depression. [3][4][5][6] Lithuania remains a country where depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Similarly, a study conducted in the United States of America found that increasing age could enhance the risk of depression in women with breast cancer [ 45 ]. Another study in Lithuania also estimated that the risk of suffering from depression in breast cancer patients older than 55 years old would be increased by 2.25 times compared to their younger counterparts [ 46 ]. These findings are in contrary to studies conducted in some of the countries which reported that the incidence of mental disorders including depression is higher among younger patients [ 36 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in the United States of America found that increasing age could enhance the risk of depression in women with breast cancer [ 45 ]. Another study in Lithuania also estimated that the risk of suffering from depression in breast cancer patients older than 55 years old would be increased by 2.25 times compared to their younger counterparts [ 46 ]. These findings are in contrary to studies conducted in some of the countries which reported that the incidence of mental disorders including depression is higher among younger patients [ 36 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a recent study done among African American population in USA found that older age increased the risk of having depression compared to the younger age in women with breast cancer [47]. Another study done in Lithuania also reported that breast cancer patients over age 55 years had a 2.25 times greater risk of suffering from depression compared to those who were younger [48].…”
Section: Discussionmentioning
confidence: 99%